TG1042 (Adenovirus-interferon-γ) in primary cutaneous B-cell lymphomas: a phase II clinical trial. - Brigitte Dreno; Mirjana Urosevic-Maiwald; Youn Kim; Joan Guitart; Madeleine Duvic; Olivier Dereure; Amir Khammari; Anne-Chantal Knol; Anna Derbij; Monika Lusky; Isabelle Didillon; Anne-Marie Santoni; et al. (PLoS ONE)
Rational While a variety of registered therapies exist for Cutaneous T Cell Lymphoma, no such therapy is available for Cutaneous B Cell Therapy. In this context we performed a phase II, open label, multicenter, non-comparative study to evaluate the efficacy and safety of repeated intra-lesional administrations of TG1042 (adenovirus-interferon-γ) in patients with relapsing primary cutaneous B-cell lymphomas (CBCL). Method Thirteen patients have been enrolled and received intralesional injections of TG1042 containing 5×10(10) viral particles into up to six lesions simultaneously. Injections were performed on days 1, 8 and 15 of each of four consecutive 28 day cycles. Results Eleven (85%) out of 13 enrolled patients showed an objective response after injections of TG1042. Seven patients (54%) exhibited complete and four (31%) displayed partial response. The median time to disease progression in the study population was 23.5 months (range 6.25 to 26+). Most commonly observed adverse events were minor to moderate flu-like symptoms, fatigue and injection site reactions. Conclusions Our study showed that treatment with TG1042 was associated with a clinical benefit in the majority of the patients with relapsing CBCL, including tumor regression, a clinically meaningful duration of response and a good treatment tolerance. Trial registration www.clinicaltrials.govNCT00394693.